BCOM - Lehman, Carol M.; DuFrene, Debbie D; Cameron-Dow, Joy; Barrett, Mary; Murphy, Wayne (South Melbourne, Victoria : Cengage Learning Australia, 2012)
This book is specifically aimed at business students studying communication skills in a business degree. In today's fast-paced business environment, communicating effectively with multiple audiences is more essential - and more challenging - than ever. This is a concise and engaging introduction to the principles of business communication. The text combines a strong emphasis on sound writing principles with practical coverage of real-world spoken, electronic, and written communication situations and strategies that play a vital role in modern business. This book is enriched with an abundance of model documents and local and global examples to help students translate communication theory into applied best practices.
Part 1: Communication foundations and analysis -- Part 2: Communication through electronic, voice and written messages -- Part 3: Communication through reports and business presentations -- Part 4: Communication for employment.
Cover title.
Includes bibliographical references and index.
Keywords: Communication in management; Business communication; Business report writing; Commercial correspondence; Australian